Mewujudkan Keadilan dalam Perlindungan Hukum Bagi Perempuan Sebagai Pribadi yang Sama di Mata Hukum Dalam Pasal 6 The Universal Declaration of Human Rights - Aisah, Putri Maharani Rahma; Arifin, Tajul; Fauzia, Ine (Pamulang Law Review, 2025)
This research is motivated by the fact that gender inequality in the legal system remains a serious issue, with women often experiencing discrimination rooted in patriarchal cultural norms. Such discrimination, reflected in both formal and customary laws, obstructs women’s access to justice. This situation contradicts Article 6 of The Universal Declaration of Human Rights, which affirms that every individual has the right to recognition and protection as an equal before the law. The study aims to analyze the barriers faced by women in obtaining fair legal treatment and to explore efforts to achieve legal equality based on human rights principles. The research employs a normative juridical approach and uses a descriptive analytical method, with data analyzed through quantitative analysis techniques. The findings reveal that gender-based violence, such as domestic violence and sexual harassment, has not received adequate attention from the legal system. These challenges are further compounded by weak law enforcement and the slow pace of legislative reforms supporting gender equality. The study underscores the necessity of ensuring legal justice for women through inclusive legal reforms and the empowerment of women.